The impact of COVID-19 on Health Science undergraduate students’ academic experience and mental health: A pilot study - Bhowmik, Jahar; Kendal, Evie; Kwa , Faith (Journal of University Teaching and Learning Practice, 2024)
The COVID-19 pandemic has created significant disruptions in teaching and learning at universities, predisposing university students to develop mental health issues which may impact their academic experience. This study evaluated the academic experience and mental health status of students enrolled in Health Science courses at Swinburne University of Technology via a mixed-methods cross-sectional survey conducted on 36 students (18+ years). Out of these students, 10 attended in-depth interviews. Results obtained from both quantitative and qualitative data analyses found high levels of stress, anxiety and depression, with more than 50% experiencing levels above the clinical thresholds. About 39% of the participants reported feeling able to concentrate on their learning when materials were delivered via an online mode. Students’ engagement through online learning was significantly disrupted, 97.2% of the respondents found it difficult to perform group work and 75% reported not being able to engage with their peers. Higher levels of stress, anxiety and depression were significantly associated with a compromised learning experience. Spearman’s Rank Correlation showed a significant negative association between stress and students’ engagement with online learning (Spearman’s rho=-0.49, p=0.003). Supporting the learning experiences along with monitoring the mental health of all university students should be of high priority for university authorities.